Pulmonary Cement Embolism - Morgado, Margarida (2023)
Vertebroplasty and kyphoplasty are widely used procedures for patients with symptomatic spinal compression fractures. Cement leakage into the paravertebral veins leading to pulmonary embolism is not an uncommon complication and the risk is increased when treating bone metastases. We present a case and images of a patient with previous vertebral compression fractures from metastatic breast cancer treated with vertebroplasty and kyphoplasty which presented imaging findings consistent with pulmonary cement embolism.   Keywords Pulmonary Embolism; Bone Cements; Vertebroplasty; Kyphoplasty; Fractures, Compression.